2008
DOI: 10.1016/j.chiabu.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple maltreatment experiences among psychiatrically hospitalized youth

Abstract: Objective-Relying on indicators coded from information collected routinely during intake assessments at a secure inpatient psychiatric facility, this study examined the extent to which different forms of maltreatment accounted for variations in youths' emotional and behavioral problems.Methods-Clinical information was reviewed for a large (N = 401) and diverse sample (mean age = 13.9 years; 53% male; 54.6% racial/ethnic minority) of youth admitted to a publicly funded psychiatric hospital. Data were drawn from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 43 publications
5
64
0
10
Order By: Relevance
“…Leenarts et al found a direct relationship between exposure to early-onset interpersonal trauma and mental health problems in girls in Dutch residential care facilities (Leenarts et al, 2013). Boxer and Terranova found that even among adolescents in a psychiatric hospital ward, maltreatment experiences accounted for variations in levels of psychopathology (Boxer & Terranova, 2008), while Gover found a higher prevalence of depression among sexually abused incarcerated youth in the US than among those who had not been sexually abused . One study also found an association between exposure to trauma and risk behavior among adolescents entering a residential treatment facility .…”
Section: B S T R a C Tmentioning
confidence: 99%
“…Leenarts et al found a direct relationship between exposure to early-onset interpersonal trauma and mental health problems in girls in Dutch residential care facilities (Leenarts et al, 2013). Boxer and Terranova found that even among adolescents in a psychiatric hospital ward, maltreatment experiences accounted for variations in levels of psychopathology (Boxer & Terranova, 2008), while Gover found a higher prevalence of depression among sexually abused incarcerated youth in the US than among those who had not been sexually abused . One study also found an association between exposure to trauma and risk behavior among adolescents entering a residential treatment facility .…”
Section: B S T R a C Tmentioning
confidence: 99%
“…Globalement, les résultats sont cohérents avec ceux obtenus auprès d'échantillons populationnels d'âge similaire lors d'études effectuées dans d'autres pays utilisant le même instrument, qui indiquent que 71 % des enfants ont été victimisés aux États-Unis (Finkelhor et al, 2005 ;2005b) et 88,4 % en Espagne (Soler et al, 2012). Les résultats correspondent également aux travaux qui ont évalué des éventails moins larges de victimisation avec des échantillons cliniques (Boxer & Terranova, 2008 ;Ford, Gagnon et al, 2011 ;Ford, Wasser et al, 2011), bien que les taux soient inférieurs parce qu'ils évaluent seulement les situations graves de maltraitance (entre 32 % et 69 %). En outre, en comparant les résultats avec ceux obtenus dans d'autres travaux espagnols, le pourcentage de victimisation est similaire et l'on constate une fréquence élevée de violence dans la vie des garçons et des fi lles (89,2 %) (Lila et al, 2008).…”
Section: Discussionunclassified
“…Diverses études révèlent davantage de violence physique chez les garçons et de victimisation sexuelle chez les fi lles (Finkelhor et al, 2005b ;Boxer & Terranova, 2008). En dépit de ces écarts, la différence est signifi cative uniquement pour la victimisation via Internet, dans laquelle les fi lles subissent plus de victimisations que les garçons.…”
Section: Discussionunclassified
“…Maltreatment in childhood and adolescence is recognised as an important psychopathological risk factor and is associated with poor psychological function in childhood [64][65][66][67][68][69][70][71] and in adolescence [68,[72][73][74][75] and in adulthood [76][77][78].…”
Section: Psychopathological Consequences Of the Child Abuse And Neglectmentioning
confidence: 99%